Nutrient Uptake and Yield of Peanuts (Arachis hypogaea L.) under Different NPK Forms and Doses - Diky Anggi Riyansyah; Andi Masnang; Asmanur Jannah (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2026)
Fertilization is important in peanut cultivation through the use of fertilizers tailored to crop requirements. This study aimed to determine the effects of NPK fertilizer form and dosage on nutrient uptake and peanut yield. The experiment was arranged in a Randomized Block Design with a 2 × 2 factorial pattern and eight replications, resulting in 32 experimental units. The treatments consisted of two factors: the first was fertilizer form, with granular and blended options. The second factor was NPK fertilizer dosage, with two levels: 200 kg ha⁻¹ and 250 kg ha⁻¹. The results showed a significant interaction between fertilizer form and dosage on plant height at 25 days after planting and net pod weight. The highest plant height reached 14.8 cm in the blending form treatment and a dose of 250 kg ha-¹, while the best net pod weight was 2,681.8 kg ha⁻¹, obtained from blending fertilizer at a dosage of 200 kg ha⁻¹. In the blended fertilizer form, N and K nutrient uptake were higher than in the granular form. Uptake of P tended to be similar across both fertilizer forms and dosages. Fertilizer dosage significantly affected crop productivity, with the highest yield obtained at 250 kg ha⁻¹.